How parental involvement in youth sports impacts on school adjustment: a dual mediation pathway via sports interest and extracurricular sports participation - Haoyuan Zheng; Zubing Xiang; Wenli Yang (Frontiers in Public Health)
IntroductionThis study aimed to examine whether parental involvement in youth sports influences Chinese adolescents’ school adjustment and to investigate the mediating roles of extracurricular sports participation and sports interest in this relationship.MethodsUsing longitudinal data from the China Education Panel Survey (CEPS) for the 2013–2014 academic year, which included 12,257 junior high school students from China, this study employed a multiple mediation model to analyze the effects of parental involvement in youth sports, sports interest, and extracurricular sports participation on adolescents’ school adjustment.ResultsThe findings revealed that: (1) Parental involvement in youth sports had a significant and independent positive effect on adolescents’ school adjustment. (2) Parental involvement in youth sports could also enhance school adjustment by increasing sports interest and promoting extracurricular sports participation, through three distinct pathways: parental involvement in youth sports → extracurricular sports participation → school adjustment; sports interest → extracurricular sports participation → school adjustment; parental involvement in youth sports → sports interest → extracurricular sports participation → school adjustment. These results elucidate the mechanisms through which parental involvement in youth sports, sports interest, and extracurricular sports participation collectively contribute to adolescents’ school adjustment, providing empirical evidence for strategies aimed at improving school adaptation.DiscussionThe study demonstrates that parental involvement in youth sports can directly enhance adolescents’ school adjustment, as well as indirectly influence it through sports interest or extracurricular sports participation individually, or via a multiple mediation of sports interest followed by extracurricular sports participation.